DEVELOPMENT OF POP-UP BOOK MEDIA BASED ON ANIMATED VIDEO ON JAPANESE OCCUPATION MATERIAL FOR STUDENTS OF GRADE XI SMAN 2 SIAK HULU: Pengembangan Media Pop-Up Book Berbasis Video Animasi Materi Pendudukan Jepang Pada Siswa Kelas XI SMAN 2 Siak Hulu - Muhammad Riski Riski; Suroyo; Asyrul Fikri (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2026)
This research aims to develop an innovative learning media in the form of a Pop-up Book integrated with animated video for teaching the topic of the Japanese occupation in Indonesia to 11th-grade students at SMAN 2 Siak Hulu. The study addresses the limited use of technology-based media in history learning, which is still dominated by conventional lectures and lacks visual learning aids. The development process adopted the ADDIE model, encompassing Analysis, Design, Development, Implementation, and Evaluation. The media was developed using Microsoft PowerPoint and enhanced with 2D and 3D visual elements, then converted into animated video format accessible via smartphones and projectors. Validation was conducted by subject matter experts and media experts, yielding "very feasible" ratings with scores of 85% and 90%, respectively. Student responses in small and large group trials also showed high feasibility scores of 81% and 89%. The results indicate that the media effectively increases student engagement, improves understanding of historical chronology, and supports independent learning. The novelty of this research lies in the digital transformation of Pop-up Book media, offering a more flexible and engaging history learning experience suitable for digital-native students. This media has potential for wider application and further development across other historical themes and subjects.